Local Religion: Complexity of Challenges and Efforts to Maintain Existence in the Pre-Reformation Era - Misbahuddin; Salsabila Usman (Journal of Islamic History, 2024)
Abstrack Pre-reformation was a difficult period for groups of Penghayat Kepercayaan/Local Religion in Indonesia. Pressure and marginalization on all fronts become part of their lives. Their options of the pressure they receive were divergent. Despite in general the sources of pressure approximately same, their ways of dealing with those challenges were determine on the quantity and regional condition confined to the intensity and implementation of the opposition. This researched was qualitative, descriptive analytic. The researched method used the Historical Research Method with sociological and anthropological. The results of the research showed that the adaptation options carried out by large groups of Local Religion in communal areas (cities) tend to take place politically and avoid physical clashes. Meanwhile, the large groups but militant in remote areas face physical opposition (group wars with other marginal communities) so that they also react with physical warfare. This situation is another effect of the newly established state which defined to many clashes of understanding in society. On the other hand, a small quantity of Local Religion in remote areas prefer to the path of peace and spread the teachings secretly. The findings in this research will guide policy makers in understanding the background, development and challenges of believers, each of which has its own uniqueness. Keywords: local religion, opposition, existence effort. REFERENCE Afandi, A. (2018). Kepercayaan Animisme-Dinamisme Serta Adaptasi Kebudayaan Hindu-Budha Dengan Kebudayaan Asli Di Pulau Lombok-NTB. Historis | FKIP UMMat, 1(1), 2. https://doi.org/10.31764/historis.v1i1.202 Armin, M. (2013). Tarekat Muhdi Akbar dalam Kehidupan Keberagaman di Selayar: Perbedaan dalam Tinjauan Etika. UIN Alauddin Makassar. Artika, I. W. (2022). The Oppressed Class in Lekra Poems. Proceedings of the 2nd International Conference on Languages and Arts across Cultures (ICLAAC 2022), 149. https://www.atlantis-press.com/proceedings/iclaac-22/125978227 Bahfiarti, T., Chotimah, I., Ilmi, D. N., & Anggriani. (2021). Komunikasi Keluarga dalam Mentransformasikan Nilai-Nilai Budaya To Lotang di Kabupaten Sidrap. Jurnal Komunikasi, 15, 170. https://doi.org/https://doi.org/10.21107/ilkom.v15i2.12419 Barton, G. (2000). Citizenship and Democracy in a Global Era. Macmilan Press Ltd. & ST. Martin’s Press Inc. Fadhil, A. (2020). Peran Komunitas Adat Karuhun Urang (AKUR) terhadap Kerukunan Umat Beragama dalam Masyarakat Multikultural di Desa Cigugur Kuningan 1985-2020. IAIN Syech Nurjati Cirebon. Huda, N. (2017). Konstruksi Ajaran Budaya Perguruan Ilmu Sejati dalam Relasinya dengan Nilai Keislaman. Analisis: Jurnal Studi Keislaman, 17, 30–31. Jufri, M., & Mukhlish, M. (2019). Akibat Hukum Pemisahan Hak Beragama dengan Hak Berkepercayaan dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Jurnal Konstitusi, 16(2), 274. https://doi.org/10.31078/jk1624 Kemendagri. (2022). Kemendagri Sosialisasikan Dokumen Kependudukan bagi Penghayat Kepercayaan di Kabupaten Kotabaru Kalsel. Dukcapil.Kemendagri.Go.Id. https://dukcapil.kemendagri.go.id/berita/baca/1279/kemendagri-sosialisasikan-dokumen-kependudukan-bagi-penghayat-kepercayaan-di-kabupaten-kotabaru-kalsel Misbahuddin. (2022a). Agressiveness of Muhammadiyah Islamic Education in Selayar (1931-1938). Al-Qalam, 28(1), 147–148. https://doi.org/http://dx.doi.org/10.31969/alq.v28i1.1034 Misbahuddin. (2022b). Sang Surya Bersinar di Tanadoang: Gerakan Persyarikatan Muhammadiyah Selayar 1928-1950. Deepublish. Najamuddin, Kasnawi, T., Agustang, A., & Suhaeb, F. (2015). Muhdi Akbar: Nursery of Local Multicultural ini Selayar. International Journal of Academic Research, 7, 82. https://doi.org/10.7813/2075-4124.2015/7-1/B.14 Nirwana, A. (2018). Local Religion: To Wani Tolotang, Patuntung dan Alu Tudolo di Sulawesi Selatan. Bahasa dan Sastra Arab. Pradnya, I. M. A. S. (2021). Eksistensi Aliran Kepercayaan Nusantara di Era Post Modern. Proseding Mistisme Nusantara Brahma Widya, 32. https://stahnmpukuturan.ac.id/jurnal/index.php/brahmawidya/ Qodim, H. (2017). Strategi Bertahan Agama Djawa Sunda (ADS) Cigugur. Kalam, 11, 342. https://doi.org/https://doi.org/10.24042/klm.v11i2.1912 Sukamto, A. (2013). Ketegangan Antar Kelompok Agama Pada Masa Orde Lama sampai Orde Baru: dari Konflik Perumusan Ideologi Negara sampai Konflik Fisik. Indonesian Journal of Theology, 1, 31. https://doi.org/https://doi.org/10.46567/ijt.v1i1.90 Wahab, A. J. (2015). Harmoni di Negeri Seribu Agama: Membumikan Teologi dan Fikih Kerukunan. PT. Alex Media Komputindo.